Voltage Stability Improvement By Using FACTS Elements With Economic Consideration - Kianersi, Hadi; Asadi, Hamid (Ciência e Natura, 2015)
In last two decades due to increasing power demand power systems are operated to their maximum operation conditions. It will cause to any problems that one of these is voltage instability. To overcome this problem Flexible AC Transmission Systems(FACTS) have been used in power systems. The FACTS devices improves system stability, reduce losses and power generation cost. Best location of FACTS devices will help to maintain bus voltages at desired level, reduce cost of these devices and improve voltage stability margins. This paper presents the methods to location and rating of FACTS devices are optimized with using weighted coefficients method and Sterength Paretto Evolutionary Algorithm(SPEA).Thyristor controlled series capacitor(TCSC)and Static Var Compensator(SVC)are also considered in this paper.